1987
DOI: 10.1002/clc.4960100210
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial bridging of coronary arteries associated with an impending acute myocardial infarction

Abstract: Summary: A 57-year-old woman developed severe substernal chest pain rddiating to the left arm accompanied hy pallor and marked diaphoresis. These symptoms appeared at rest, lasted 45 minutes, and terminated spntaneously. The patient had been treated for mild hypertension during the last 6 months. An ECG tracing obtained at the beginning of treatment was unremarkable. However, an ECG tracing recorded shortly after the end of the symptoms showed T-wave inversion in all anterior leads. Coronary arteriography was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 7 publications
1
22
0
1
Order By: Relevance
“…Some case reports have indicated that a relationship exists between MB and major cardiac events, such as myocardial infarction [12][13][14][15][16][17] and cardiac sudden death. [18][19][20][21] Several factors may account for MB-related myocardial ischemia.…”
Section: Cardiac Events Associated With Myocardial Bridgingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some case reports have indicated that a relationship exists between MB and major cardiac events, such as myocardial infarction [12][13][14][15][16][17] and cardiac sudden death. [18][19][20][21] Several factors may account for MB-related myocardial ischemia.…”
Section: Cardiac Events Associated With Myocardial Bridgingmentioning
confidence: 99%
“…[1][2][3] The frequency of MB has been reported to range from 5.4 to 85% in autopsy series [4][5][6] and from 0.5 to 29.4% on coronary angiography. 1,[6][7][8][9][10][11] Although it remains to be determined how MB affects the cardiovascular system, MB has been associated with myocardial infarction [12][13][14][15][16][17] and sudden cardiac death, [18][19][20][21] and coronary spasm is thought to be one factor connecting cardiac events and MB. 13,22,23 However, it has yet to be verified that coronary spasm is more frequent in patients with MB.…”
Section: Introductionmentioning
confidence: 99%
“…13,18,20 However, it has been reported that MB may be responsible for flow disturbances, myocar dial ischemia and infarction, arrhythmia and sudden death. 1,2,[4][5][6][7][8]13 In our study, 3 patients were thought to have ischemiarelated MB. MB is also a problem during bypass surgery.…”
Section: Discussionmentioning
confidence: 61%
“…15 The location of the MB in our study was most commonly in the midLAD, in concordance with previous reports. 6,8 Generally, the incidence of MB is between 0.5% and 2.5% angiographically and between 15% and 85% pathologically. 1,2 In our study, the incidence of MB (6.42%) was higher than reported in an angiographic series, but similar to that reported in some 16slice MDCT series.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, connections with unstable angina, acute myocardial infarction, arrhythmia, and sudden death have been reported. [18][19][20][21] In the treatment of MB, beta-blockers and nondihydropyridine calcium-channel blockers should be considered first, due to their negative inotropic and chronotropic effects. [22] Nitrates used in coronary artery stenosis should be avoided due to their effects on systolic contraction rate and attendant worsening of symptoms.…”
Section: Discussionmentioning
confidence: 99%